2012
DOI: 10.1186/1471-2164-13-269
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and proteomic analysis of the formation of Phakopsora pachyrhizi appressoria

Abstract: BackgroundPhakopsora pachyrhizi is an obligate fungal pathogen causing Asian soybean rust (ASR). A dual approach was taken to examine the molecular and biochemical processes occurring during the development of appressoria, specialized infection structures by which P. pachyrhizi invades a host plant. Suppression subtractive hybridization (SSH) was utilized to generate a cDNA library enriched for transcripts expressed during appressoria formation. Two-dimensional gel electrophoresis and mass spectroscopy analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…In the same way, the comparison of the 9234 H. vastatrix transcript to a collection of ESTs and proteins differentially expressed in P. pachyrhizi appressoria (Stone et al, 2012) shows a very limited number of genes in common between both studies (Supplementary Data 14). Interestingly however, the comparison of 4492 P. pachyrhizi haustorial ESTs (Link et al, 2013) to the 9234 H. vastatrix transcripts identified 1668 hits to 1132 unique H. vastatrix transcripts.…”
Section: Resultsmentioning
confidence: 95%
“…In the same way, the comparison of the 9234 H. vastatrix transcript to a collection of ESTs and proteins differentially expressed in P. pachyrhizi appressoria (Stone et al, 2012) shows a very limited number of genes in common between both studies (Supplementary Data 14). Interestingly however, the comparison of 4492 P. pachyrhizi haustorial ESTs (Link et al, 2013) to the 9234 H. vastatrix transcripts identified 1668 hits to 1132 unique H. vastatrix transcripts.…”
Section: Resultsmentioning
confidence: 95%
“…We conducted an enrichment analysis in Blast2GO to identify GO terms that were overrepresented in each genotype for which P. pachyrhizi reads were obtained, susceptible (BRS231) and resistant (PI561356), as well as GO terms that were conserved and overrepresented among different infection structures, such as germinated urediniospores and appressoria ( Stone et al , 2012 ), haustoria ( Link et al , 2014 ), and leaf lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Since the nuclear genome of P. pachyrhizi has not yet been sequenced, most of the molecular information about this pathogen has been obtained from work involving transcriptome sequencing associated with bioinformatics analyses. Thus, a moderate repertoire of candidate gene sequences expressed in germinated urediniospores, appressorium, haustorium, and uredinia have become available ( Posada-Buitrago and Frederick, 2005 ; Tremblay et al , 2009 , 2012 , 2013 ; Stone et al , 2012 ; Link et al , 2014 ; Carvalho et al , 2016 ). Most of these studies focused on the characterization of specific molecular mechanisms during the infection process, with a concentration on analyses of specific structures of the pathogen, such as the urediniospores and haustorium, or of the total infected leaf.…”
Section: Introductionmentioning
confidence: 99%
“…Dikaryotic aeciospores and urediniospores enter the host leaf through openings in the stomata, after appressorium differentiation (Voegele et al, 2009). Several transcriptomic analyses of appressoria formation of urediniospores led to identification of the genes responsible for metabolism and regulation of the cell division cycle, indicating that this structure plays an active role in the penetration process (Hu et al, 2007;Stone et al, 2012;Talhinhas et al, 2014). Urediniospores from the soybean rust fungus directly penetrate their host through the epidermis, in a similar manner to basidiospores of heteroecious fungi, and form an appressorium with a high cell turgor pressure of 5.13 MPa (Loehrer et al, 2014a), which correlates with what has been observed in other fungal plant pathogens (Ryder & Talbot, 2015).…”
Section: Early Stages Of Infection: Host Penetration and Haustorium Fmentioning
confidence: 99%